Challenges of Nuclear Waste Governance An International Comparison Volume II (Energiepolitik und Klimaschutz. Energy Policy and Climate Protection,, 2018)
This is volume two of a comparative analysis of nuclear waste governance and public participation in decision-making regarding the storage and siting of high-level radioactive waste and spent fuel in different countries. The contributors examine both the historical and current approaches countries have taken to address the wicked challenge of nuclear waste governance. The analyses discuss the regulations, technology choices, safety criteria, costs and financing issues, compensation schemes, institutional structures, and approaches to public participation found in each country. Contents Technical, Political, and Socio-Economic Challenges of Nuclear Waste Governance "The Big 4" - China, Russia, South Korea and Japan The Eastern European Countries Nuclear Waste Governance in Argentina, Brazil, Canada, and South Africa Target Groups Energy (policy) experts, nuclear energy experts and practitioners, political and social scientists, economists, engineers, decision makers and consultants, civil society organizations The Editors Achim Brunnengräber, Maria Rosaria Di Nucci, Ana María Isidoro Losada, Lutz Mez, Environmental Policy Research Centre, Freie Universität Berlin, and Miranda A. Schreurs, Bavarian School of Public Policy, Technical University of Munich, were members of the project "Multi Level Governance-Perspective on Nuclear Waste Disposal" within the research platform ENTRIA (2013-2017).